Efektivitas Teknik Self-Management Melalui Konseling Kelompok Untuk Mengelola Emosi Siswa Di SMP Negeri 02 Umbulsari - M.Rizki Maulana; Muhammad Fikri Fauzi; Faisol Hakim (Jurnal Ilmu Bimbingan dan Konseling, 2026)
The ability to manage emotions is a crucial skill for junior high school students, as it influences their learning processes, social relationships, and adjustment to the school environment. However, some students still struggle with emotional control, exhibiting tendencies such as irritability, oversensitivity, and a lack of self-regulation. This study aimed to determine the effectiveness of self-management techniques—delivered through group counseling—in managing the emotions of students at SMP Negeri 02 Umbulsari. A quantitative approach was employed using a pre-experimental design, specifically the one-group pretest-posttest model. The study sample, selected via purposive sampling, consisted of eight students in the experimental group. Data were collected using an emotion management questionnaire comprising 30 valid items (Cronbach’s Alpha = 0.893) and analyzed using an independent sample t-test. The results yielded a significance value (sig. 2-tailed) of 0.000. Since the sig. (2-tailed) value of 0.000 was less than 0.05, the decision was made to accept the alternative hypothesis (Ha) and reject the null hypothesis (Ho). Thus, it can be concluded that self-management techniques administered through group counseling are effective for managing student emotions at SMP Negeri 02 Umbulsari.